CES 2021
DOI: 10.15179/ces.23.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Corporate Governance: Evidence from Kosovo’s Banking Sector

Abstract: This study identifies and assesses the impact and effect of corporate governance (CG), as a good practice mechanism, as well as some specific financial indicators on the performance of the banking sector in Kosovo. The data used in the research are defined as secondary data that include nine (9) commercial banks and cover the period 2013–2020. The analysis applied to data processing is the dynamic approach through 2SLS estimation for the dependent variables ROA, ROE, and NIM. The results obtained at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The main components of GCG that are recognized to influence funding decisions are board size, board independence, executive compensation, and executive camp. Implementing GCG can prevent decision-making mistakes that automatically increase the company's value, which is reflected in profitability (Durguti & Kryeziu, 2021). Research conducted by Anjani & Yadnya (2017) found that GCG positively and significantly affects company profitability.…”
Section: Introductionmentioning
confidence: 99%
“…The main components of GCG that are recognized to influence funding decisions are board size, board independence, executive compensation, and executive camp. Implementing GCG can prevent decision-making mistakes that automatically increase the company's value, which is reflected in profitability (Durguti & Kryeziu, 2021). Research conducted by Anjani & Yadnya (2017) found that GCG positively and significantly affects company profitability.…”
Section: Introductionmentioning
confidence: 99%